2014
DOI: 10.5551/jat.23390
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eicosapentaenoic Acid Treatment on Epicardial and Abdominal Visceral Adipose Tissue Volumes in Patients with Coronary Artery Disease

Abstract: Aim: Epicardial adipose tissue (EAT) is a pathogenic fat depot that may be associated with coronary atherosclerosis and cardiovascular events. Because eicosapentaenoic acid (EPA) has been reported to exert cardiovascular protective effects, we aimed to assess the effects of EPA on the volume of visceral adipose tissue, including EAT and abdominal visceral adipose tissue (AVAT), using multislice computed tomography (CT). A similar negative correlation in these parameters was also observed for the EAT volume. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 54 publications
(51 reference statements)
0
8
1
Order By: Relevance
“…For practical reasons we did not measure inflammatory responses in visceral fat, a depot known to be inherently more immune-cell infiltrated than subcutaneous fat. Some investigators have reported positive effects of v-3 fatty acid supplements on visceral fat (46,47), and others have noted that greater self-reported v-3 fatty acid intakes are negatively associated with visceral fat and percentage of body fat in healthy children (48). We cannot know whether there might have been a beneficial effect of v-3 fatty acids on visceral fat inflammation in our participants, but if there was it did not improve inflammatory markers (26) or insulin sensitivity.…”
Section: Discussioncontrasting
confidence: 40%
“…For practical reasons we did not measure inflammatory responses in visceral fat, a depot known to be inherently more immune-cell infiltrated than subcutaneous fat. Some investigators have reported positive effects of v-3 fatty acid supplements on visceral fat (46,47), and others have noted that greater self-reported v-3 fatty acid intakes are negatively associated with visceral fat and percentage of body fat in healthy children (48). We cannot know whether there might have been a beneficial effect of v-3 fatty acids on visceral fat inflammation in our participants, but if there was it did not improve inflammatory markers (26) or insulin sensitivity.…”
Section: Discussioncontrasting
confidence: 40%
“…The superior border for measuring the EAT volume was set at the lower surface of the left pulmonary artery origin. The inferior border for the measurement was set at the left ventricular apex 19) . The EAT area was calculated by tracing an ROI that included the heart and EAT.…”
Section: Eat Volume Measurement With Multislice Ctmentioning
confidence: 99%
“…CT is the most frequently applied imaging technique to identify and measure the volume and thickness of EAT in clinical practice . With the high spatial resolution and axial scan, EAT could be easily distinguished from myocardium and paracardial adipose tissue particularly after application of iodine contrast agent . However, the application of CT is limited due to exposure of ionizing radiation especially when frequent assessment is needed (Figure ).…”
Section: The Link Between Af Obesity and Adipose Tissuementioning
confidence: 99%